Operasional Perbankan Berbasis Mobile Banking: Kemudahan, Keamanan, dan Tantangan - Annura Nazwa; Rihan Rizky; Tierra Kresna (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Mobile banking has become a core component of modern banking operations, transforming conventional services into more accessible and efficient digital systems. This study examines mobile banking operations by focusing on three key aspects: convenience, security, and operational challenges. The findings indicate that ease of use plays a crucial role in encouraging customer adoption and increasing transaction frequency, as intuitive interfaces and real-time services enhance user satisfaction. Security emerges as a fundamental pillar in sustaining customer trust, supported by layered authentication systems and regulatory standards designed to mitigate cyber risks. However, the rapid growth of mobile banking also presents operational challenges, including system stability, disparities in digital literacy, human resource readiness, and the need to comply with evolving regulations. These challenges highlight the importance of adaptive operational management and continuous system improvement. Overall, the study concludes that successful mobile banking implementation requires not only technological innovation but also strong regulatory support, effective risk management, and ongoing customer education to ensure sustainable digital banking operations.